2014
DOI: 10.3109/09553002.2014.887869
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction of cardiomyocytes and subsequent fibrosis after irradiation and neoadjuvant chemotherapy

Abstract: The study suggests that the induced cardiac remodelling begins with the reduction of intramyocardial vessels in the left ventricle tissue. The main consequence is the loss of cardiomyocytes through apoptosis, leading to the replacement of healthy tissue by fibrous tissue. It was observed that the damage caused by the combination of irradiation and chemotherapy induced functional alterations that did not occur when the animals were only irradiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
2
26
1
Order By: Relevance
“…Besides the FOLFOX-induced pathologic changes in the myocardial tissue, impaired LV function was detected and the decrease of LVEF after FOLFOX correlated to h-FABP level and myocardial fibrosis. These results are in accordance with several recent preclinical studies, which also showed an increased level of apoptosis, myocardial fibrosis, and decreased LVEF after treatment with anthracycline-based chemotherapy [35][36][37][38] and with the series of reports that showed reduced LVEF following 5-FU-based chemotherapy in humans [39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 92%
“…Besides the FOLFOX-induced pathologic changes in the myocardial tissue, impaired LV function was detected and the decrease of LVEF after FOLFOX correlated to h-FABP level and myocardial fibrosis. These results are in accordance with several recent preclinical studies, which also showed an increased level of apoptosis, myocardial fibrosis, and decreased LVEF after treatment with anthracycline-based chemotherapy [35][36][37][38] and with the series of reports that showed reduced LVEF following 5-FU-based chemotherapy in humans [39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 92%
“…Although previous studies have demonstrated radiation-induced apoptosis in animal models of local heart irradiation (30, 31), we typically do not observe large numbers of apoptotic cells at the 6 month time point in experiments with local heart irradiation in rat and mouse models (18). In accordance with our previous studies, radiation did not modify the number of apoptotic cells in wild-type mice.…”
Section: Discussioncontrasting
confidence: 83%
“…Myofibroblasts are abundant components of the reactive tumour microenvironment and are mostly accountable for the development of fibrosis [ 21 ], one of the side-effects of cancer therapy [ 31 ]. Fibroblast-to-myofibroblast differentiation increases in the stroma with age as well, resulting in an increased incidence of fibrosis-associated diseases, such as cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%